Alignment Model of Expectations with Actual Lifetime of Mainpump Components on Heavy Equipment - Febrianto, Anggi; Suef, Mokh; Saiful Hakim, Muhammad (Department of Mechanical Engineering, Vocational College, Gadjah Mada University., 2025)
This research focuses on the importance of optimal machine performance in various industrial sectors, emphasising the reliability of each component as a crucial factor in maintaining productivity and operational efficiency. In this context, specific research was conducted to analyse the difference between the expected life of components and the actual life achieved in the field. There is a significant knowledge gap associated with the mismatch between expected and actual component life, potentially leading to unexpected increases in operating costs and decreases in efficiency. This study used survey methodology and linear regression analysis to evaluate the relationship between the expected and actual age of mainpump components on Komatsu PC200 units. The main results showed that the actual life of the components tended to be lower than the expected life, with an average gap of 3,257 hours, indicating the need for adjustments to maintenance and replacement strategies. The analysis also revealed that factors such as severe operational conditions and suboptimal maintenance methods contributed to this mismatch. The implications of this study point to the importance of implementing a more adaptive and data-driven maintenance strategy to improve operational efficiency and minimise unexpected downtime.